Quality of Democracy Makes a Difference, but Not for Everyone: How Political Interest, Education, and Conceptions of Democracy Condition the Relationship Between Democratic Quality and Political Trust - Mauk, Marlene (Frontiers in Political Science, 2021)
In light of recent crises, not least the COVID-19 pandemic, citizen trust in the political system has been highlighted as one of the central features ensuring citizen compliance and the functioning of democracy. Given its many desirable consequences, one of the key questions is how to increase political trust among ordinary citizens. This paper investigates the role of democratic quality in determining citizens’ trust in the political system. While we know that citizens’ evaluations of democratic performance are a strong predictor of political trust, previous research has shown that trust is not always higher in political systems with higher democratic quality, indicating that democratic performance evaluations do not always correspond to actual democratic quality. Several moderating factors may account for this disconnect between democratic quality and citizens’ evaluations of democratic performance and, ultimately, political trust. For one, citizens may receive different information about the political system; second, they may process this information in different ways; and third, they may have different standards of what democratic quality ought to be. Using survey data from three rounds of the World Values Survey (2005–2020) and aggregate data on democratic quality and other macro determinants of political trust from the V-Dem project and World Development Indicators for 50 democracies around the world, this contribution empirically investigates the complex relationship between democratic quality, democratic performance evaluations, and political trust in multi-level moderated mediation models. Its findings demonstrate that democratic quality affects political trust indirectly through citizens’ democratic performance evaluations and that this indirect effect is stronger for citizens with higher political interest, higher education, and especially those with more liberal conceptions of democracy.